2013
DOI: 10.1002/j.2055-2335.2013.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Severity Scores and Prescribing Antibiotics for Community‐Acquired Pneumonia at an Australian Hospital

Abstract: Aim To evaluate the use of pneumonia severity scores for diagnosing community‐acquired pneumonia (CAP) and to assess whether antibiotic prescribing was compliant with guidelines as determined by the calculated pneumonia severity score. Method A retrospective chart review was undertaken of consecutive adults admitted via the emergency department with a diagnosis of CAP during a 6‐month period. Charts were reviewed for symptoms and radiographic evidence of pneumonia and for recorded pneumonia severity scores. Pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Studies reveal that the documented use of a pneumonia severity score is extraordinarily low (5%). 24 , 25 Besides, several studies showed a very poor recording of the CAP severity score. 18 , 20 , 26 Assessing the CURB-65 score helps physicians to classify patients and select appropriate antimicrobial therapy concerning the patient site of care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reveal that the documented use of a pneumonia severity score is extraordinarily low (5%). 24 , 25 Besides, several studies showed a very poor recording of the CAP severity score. 18 , 20 , 26 Assessing the CURB-65 score helps physicians to classify patients and select appropriate antimicrobial therapy concerning the patient site of care.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found the use of a scoring tool was rarely recorded in medical notes (11.9%). A recent Australian study showed even poorer documentation of severity tools, where only one out of 69 patients had a severity score documented . In our study, even when a severity score was documented, the TG14 recommended tools (SMART‐COP/CORB) were only utilised in 1% of cases, other severity scoring tools such as CURB65 and PSI were used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Maxwell et al reveals that documented use of a pneumonia severity score in Australian hospitals is extraordinarily low (5%) 11. Numerous studies have revealed that there is poor recording of CAP severity scores in clinical documentation 12–14. At our institution, the CORB score was not documented in any of the medical records of over 250 patients admitted with CAP in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…11 Numerous studies have revealed that there is poor recording of CAP severity scores in clinical documentation. 1214 At our institution, the CORB score was not documented in any of the medical records of over 250 patients admitted with CAP in 2012. This may reflect a lack of awareness or perceived usefulness of pneumonia severity assessment tools.…”
Section: Introductionmentioning
confidence: 99%